Detection of relapsing fever Borrelia spp., Bartonella spp. and Anaplasmataceae bacteria in argasid ticks in Algeria. - Ismail Lafri; Basma El Hamzaoui; Idir Bitam; Hamza Leulmi; Reda Lalout; Oleg Mediannikov; Mohamed Chergui; Mohamed Karakellah; Didier Raoult; Philippe Parola (Public Library of Science (PLoS), 2017)
Argasid ticks (soft ticks) are blood-feeding arthropods that can parasitize rodents, birds, humans, livestock and companion animals. Ticks of the Ornithodoros genus are known to be vectors of relapsing fever borreliosis in humans. In Algeria, little is known about relapsing fever borreliosis and other bacterial pathogens transmitted by argasid ticks.Between May 2013 and October 2015, we investigated the presence of soft ticks in 20 rodent burrows, 10 yellow-legged gull (Larus michahellis) nests and animal shelters in six locations in two different bioclimatic zones in Algeria. Six species of argasid ticks were identified morphologically and through 16S rRNA gene sequencing. The presence and prevalence of Borrelia spp., Bartonella spp., Rickettsia spp. and Anaplasmataceae was assessed by qPCR template assays in each specimen. All qPCR-positive samples were confirmed by standard PCR, followed by sequencing the amplified fragments. Two Borrelia species were identified: Borrelia hispanica in Ornithodoros occidentalis in Mostaganem, and Borrelia cf. turicatae in Carios capensis in Algiers. One new Bartonella genotype and one new Anaplasmataceae genotype were also identified in Argas persicus.The present study highlights the presence of relapsing fever borreliosis agents, although this disease is rarely diagnosed in Algeria. Other bacteria of unknown pathogenicity detected in argasid ticks which may bite humans deserve further investigation.